Porous silicon–polycaprolactone composites for orthopaedic tissue engineering - Henstock, James Rolleston (2009)
Silicon is an essential element in human nutrition, with the symptoms of a silicon-deficient diet being abnormal bone development (Carlisle, 1972). Similarly, animals and bone forming osteoblast-like cells in vitro show an increase in bone growth when supplemented with the soluble, bioavailable form of silicon, orthosilicic acid [Si(OH4)] (Carlisle, 1988). Certain bioactive glass compositions can form a strong chemical bond with bone, doing so by dissolving to form a solution that includes orthosilicic acid which re-polymerises to form a hydrated silica gel layer that adsorbs growth factors, supports cell growth and acts a nucleation bed for bone mineral (Hench, 1980). Bioactive glass degradation products alone have also been shown to significantly enhance the activity of osteoblasts in vitro (Xynos et al, 2001).